Lost and Found: Hoa Hakananai'a and the Orongo "Doorpost" - Van Tilburg, Jo Anne (Waka Kuaka, 2015)
The provenance of the Orongo "doorpost" before its removal from Rapa Nui in 1917 is established relative to the collection history of the basalt statue Hoa Hakananaia, removed in 1868. Both objects were collected from the same secondary site context at Orongo during a "liminal" period in Rapanui history, when traditional social bonds were tenuous and colonials and collectors regarded Rapanui objects as curios or trade objects. Impromptu Rapanui performances reinforced community identity and re-assimilated both objects into an innovated context before they were removed from Rapa Nui forever.